School Leadership and Management in Sindh Pakistan: Examining Headteachers' Evolving Roles, Contemporary Challenges, and Adaptive Strategies - Dhani Bux Shah; David Gurr; Lawrie Drysdale (MDPI AG, 2024)
This research investigates headteachers' leadership and management roles and challenges in leading government secondary schools in Sindh, Pakistan. Employing a qualitative hermeneutic phenomenology methodology, forty semi-structured interviews were conducted with twenty headteachers. The thematic analysis of the data explored that headteachers were performing several academic and administrative-focused responsibilities, although their involvement was more administrative than academic and entailed more management than leadership. However, headteachers faced enormous challenges in leading and managing their schools. Some critical challenges were a lack of basics in terms of clean water, reliable electricity, and sufficient school furniture. Others included a lack of funds, a shortage of teachers, managing professionally weak teachers, teacher union issues and a lack of authority. Nevertheless, some headteachers were making admirable efforts to address these challenges. This research may open a window to understanding the roles and challenges of headteachers and inform policymakers of how-to better support headteachers in leading their schools successfully in the 21st century.